The Neural Signals of the Superior Ovarian Nerve Modulate in an Asymmetric Way the Ovarian Steroidogenic Response to the Vasoactive Intestinal Peptide - Rosas, Gabriela; Linares, Rosa; Ramírez, Deyra A.; Vieyra, Elizabeth; Trujillo, Angélica; Domínguez, Roberto; Morales-Ledesma, Leticia (Frontiers in Physiology, 2018)
The superior ovarian nerve (SON) provides neuropeptide-Y, norepinephrine and vasoactive intestinal peptide (VIP) to the ovaries. Ovarian steroidogenesis is modulated by the SON. In the cyclic rat, the acute steroidogenic response to ovarian microinjection of VIP is asymmetric and varies during the estrous cycle. In the present study, we analyze whether the differential effects of VIP in each ovary are modulated by the neural signals arriving through the SON. Cyclic female rats were submitted on diestrus-1, diestrus-2, proestrus, or estrus to a unilateral section of the SON, and immediately afterwards, the denervated ovary was either microinjected or not with VIP. Animals were sacrificed one hour after treatment. The injection of VIP into the left denervated ovary performed on diestrus-1 decreased progesterone levels in comparison with the left SON sectioning group; similar effects were observed on proestrus when VIP was injected into either of the denervated ovaries. Compared to the left SON sectioning group, VIP treatment into the left denervated ovary on diestrus-2 or proestrus decreased testosterone levels, whereas on diestrus-1, proestrus or estrus, the same treatment resulted in higher estradiol levels. Compared to the right SON sectioning group, VIP injected into the right denervated ovary yielded higher testosterone levels on diestrus-1 and estrus and lower testosterone levels on proestrus. VIP injection into the right denervated ovary increased estradiol levels on diestrus-2 or estrus while decreasing them on proestrus. Our results indicate that in the adult cyclic rat, the set neural signals arriving to the ovaries through the SON asymmetrically modulate the role of VIP on steroid hormone secretion, depending on the endocrine status of the animal. The results also support the hypothesis that the left and right ovary respond differently to the VIPergic stimulus.